Electron Charge Density Distribution from X-Ray Diffraction Study of the 4-Methoxybenzenecarbothioamide Compound. (14th August 2013) - Drissi, Mokhtaria; Chouaih, Abdelkader; Megrouss, Youcef; Hamzaoui, Fodil
Abstract : The molecular electron charge density distribution of the title compound is described accurately using the multipolar model of Hansen and Coppens. The net atomic charge and the in-crystal molecular dipole moment have been determined in order to understand the nature of inter- and intramolecular charge transfer. The study reveals the nature of intermolecular interactions including charge transfer and hydrogen bonds in the title compound. In this crystal, the molecules form dimers via N–H⋯ S intermolecular hydrogen bonds. The dimers are further linked by C–H⋯ O hydrogen bonds into chains along the c crystallographic axis. This study has also allowed us to determine the electrostatic potential and therefore locate the electropositive part and the electronegative part in molecular scale of the title compound.